2022
DOI: 10.1002/aur.2718
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the fecal microbiota in Chinese children with autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is associated with altered gut microbiota. However, there has been little consensus on the altered bacterial species and studies have had small sample sizes. We aimed to identify the taxonomic composition and evaluate the changes in the fecal microbiota in Chinese children with ASD by using a relatively large sample size. We conducted a case–control study of 101 children with ASD and 103 healthy controls in China. Demographic information and fecal samples were collected, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
2
16
1
Order By: Relevance
“…A correlation between alpha diversity and the abundances of Bacteroides, Faecalibacterium , and Oscillospira and the Childhood Autism Rating Scale (CARS) total score was observed [ 32 ]. The opposite was found in the study of Xie et al (2022) [ 56 ].…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…A correlation between alpha diversity and the abundances of Bacteroides, Faecalibacterium , and Oscillospira and the Childhood Autism Rating Scale (CARS) total score was observed [ 32 ]. The opposite was found in the study of Xie et al (2022) [ 56 ].…”
Section: Resultsmentioning
confidence: 55%
“…Lower alpha diversity (microbial diversity within the same group’s samples) in ASD patients was described in ten studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], while in thirteen cases, higher alpha diversity was found [ 19 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Another eleven studies did not reveal any significant differences in alpha diversity between ASD patients and healthy controls [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In the rest of the studies, information about alpha diversity differences were not provided [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…In phylum level, Proteobacteria was found to be increased in autistic samples in five studies 8,9,12,40,56 . In contrast, Zou et al found that Proteobacteria was decreased in children with ASD 39 .…”
Section: Resultsmentioning
confidence: 90%
“…In phylum level, Proteobacteria was found to be increased in autistic samples in five studies. 8,9,12,40,56 In contrast, Zou et al found that Proteobacteria was decreased in children with ASD. 39 Actinobacteria was found to be increased in autistic individuals in four studies, 8,40,47,56 while Ding et al reported opposite results.…”
Section: Specific Phyla and Genus Level Differencesmentioning
confidence: 93%
“… 18 Changes in the gut microbiota may be involved in the pathogenesis of gastrointestinal symptoms in children with ASD, including significant increases in the relative abundance of Actinobacteria and Proteobacteria . 19 Compared with neurotypical children, the development of gut microbiota in children with ASD was relatively stagnant and gradually deviated from the normal track. There was no significant change in alpha diversity with age in children with ASD, the early microbiota was unstable and immature and the common bacteria was difficult in colonization.…”
Section: Autism Spectrum Disorder and Gut Microbiotamentioning
confidence: 99%